Reducing shrinkage cracking of structural concrete through the use of admixtures - Chun, Yoon-moon; Naik, Tarun R.; Kraus, Rudolph N. (Wisconsin Highway Research Program, 2006)
Shrinkage-reducing admixtures (SRAs) from three manufacturers (SRA-1, Eucon SRA from Euclid; SRA-2, Eclipse Plus from Grace; and SRA-3, Tetraguard AS20 from Degussa) were evaluated in Wisconsin Department of Transportation (WisDOT) Grade A no-ash, Grade A-FA Class C fly ash, and selected high-cementitious concrete mixtures. The three SRAs showed similar performance in reducing the drying shrinkage and autogenous shrinkage of concrete. SRAs eliminated much of the initial drying shrinkage of concrete. They reduced the 4-day drying shrinkage for Grade A and A-FA concrete mixtures by up to 67 to 83%. The 28-day drying shrinkage was reduced by up to 48 to 66%. To minimize the drying shrinkage of concrete, use of the following amounts of SRA is recommended: (1) 25 fl oz/100 lb of cement (1.6 L/100 kg of cement), or 1.1 gal/cu yd (5.5 L/cu m), for Grade A concrete; and (2) 40 fl oz/100 lb of cementitious materials (2.6 L/100 kg of cementitious materials), or 1.75 gal/cu yd (8.7 L/cu m), for Grade A-FA concrete. In most cases, SRA-1 and SRA-3 worked like water-reducing admixtures and often increased the strength and the resistance to chloride-ion penetration. SRA-2 sometimes decreased the strength and did not considerably affect the chloride-ion penetrability. All three SRAs did not influence the changes in air content and slump of fresh concrete mixtures during the first hour. Use of crushed dolomitic limestone led to the lowest early-period drying shrinkage, followed by semi-crushed river gravel, and crushed quartzite stone. Later on however, the drying shrinkage became similar, river gravel often leading to the highest late-period drying shrinkage. Use of 30% more cement and fly ash resulted in either similar or higher autogenous shrinkage, and either similar or lower drying shrinkage.
107 p.
Keywords: Concrete; Quartzite; Shrinkage; Gravel; Fly ash; Admixtures; Air content; Strength of materials; Expansive concrete; Cracking; Crushed limestone